(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2023)
The contribution offers a review of the main existing guidelines and policies on genomic testing in the Italian context, with specific reference to the issue of informed consent, the protection of minors and adults incapable of giving informed consent, and genetic counseling. To complete the framework of ethical guidelines at the national level, the article also recalls the existing indications on the ethics of genomic research.